2016
DOI: 10.1103/physreve.93.012126
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical thermalization in Bose-Hubbard systems

Abstract: We numerically study a Bose-Hubbard ring of finite size with disorder containing a finite number of bosons that are subject to an on-site two-body interaction. Our results show that moderate interactions induce dynamical thermalization in this isolated system. In this regime the individual many-body eigenstates are well described by the standard thermal Bose-Einstein distribution for well-defined values of the temperature and the chemical potential which depend on the eigenstate under consideration. We show th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…On the experimental side, an extreme degree of isolation and control has been achieved, such as in the case of ultracold quantum gases [60], trapped ions [61] and also NMR [62]. On the theoretical side, the use of the Hubbard model [53] has proven useful to address the dynamics of strongly-interacting many-body systems [63][64][65]. In addition, for spin systems, numerical studies have provided evidence indicating that the competence between disorder and interactions may lead to highly non-trivial dynamical phase diagrams [115,116].…”
Section: Closed Quantum Systems: To Equilibrate or To Localize?mentioning
confidence: 99%
“…On the experimental side, an extreme degree of isolation and control has been achieved, such as in the case of ultracold quantum gases [60], trapped ions [61] and also NMR [62]. On the theoretical side, the use of the Hubbard model [53] has proven useful to address the dynamics of strongly-interacting many-body systems [63][64][65]. In addition, for spin systems, numerical studies have provided evidence indicating that the competence between disorder and interactions may lead to highly non-trivial dynamical phase diagrams [115,116].…”
Section: Closed Quantum Systems: To Equilibrate or To Localize?mentioning
confidence: 99%
“…These studies demonstrated the stability and efficiency of S(E)-computations confirming validity of the DTC for many-body interacting quantum systems. The dynamical thermalization of an individual eigenstate was also demonstrated in [33,34]. At present the interest of many-body interacting quantum systems is also growing in the context of many-body localization (MBL) and the eigenstate thermalization hypothesis (ETH) (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the spectral characteristics in a many-body system can be exploited to understand, engineer and control the system's dynamics, making such models and their experimental realizations interesting for the study of quantum thermalization and non-equilibrium transport phenomena, see e.g. [5,11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%